Monogamy : a novel - Miller, Sue, 1943- (Harper, an imprint of HarperCollinsPublishers, 2020)
Derailed by the sudden passing of her husband of thirty years, an artist on the brink of a gallery opening struggles to pick up the pieces of her life before discovering harrowing evidence of her husband's affair.